Ocorrência De Metatrichia Robusta Kröber (Diptera: Scenopinidae) Na Amazônia E Sua Distribuição Sazonal - Rafael, José Albertino; Ale, Rosaly A. (Acta Amazonica, 1983)
The geographical distribution of Metatrichia robusta Kröber is increased to include the Amazon Basin in northern South America, and the seasonal adult population fluctuations of this species are registered, showing a higher populacional density during the dry months (July -December).